The influence of parenting styles and environment on student morality based on educational level - Jayadi, Rihal; Rejeki, Sri; Muttaqien, Zedi; Garba, Malami Muhammad (CAHAYA PENDIDIKAN, 2024)
This study aims to examine the effect of parenting and environment on student morale based on education level. This research method uses Meta-Analysis, researchers use data from 68 studies that meet the criteria and standards of data completeness from each level of education, the estimation of complete data shows an effect value of 1.130 which is included in the high effect category. However, further analysis revealed variations in this effect at each level of education. Results showed that at the kindergarten level, the effect of parenting and environment by education level had a medium effect (ES = 0.716), while at the primary school level the effect increased to high (ES = 1.097). At the junior high school level, the effect reached a very high level (ES = 1.749), but decreased slightly at the senior high school level but still fell into the high effect category (ES = 1.054). These findings highlight the importance of parents and the environment in shaping students' morals and the need for developmentally appropriate approaches at each level of education. That is, the results of this meta-analysis provide a deeper understanding of the complex dynamics between parenting, environment and student morale in an educational context.